Research on the Integration and Development of AI Technology and Art in the New Era - houzhi, Jiang (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
Driven by the rapid iteration of intelligent technologies (e.g., AI, virtual reality, real-time rendering), the animation industry is shifting from traditional creation to intelligent production. The growing synergy and contradictions between technological innovation and artistic expression make their in-depth integration a key to high-quality industrial development—this forms the study’s core background. This research aims to analyze the internal logic, existing problems, and optimization paths of such integration, providing theoretical and practical support for animation creation and industry growth. Methodologically, it combines literature research (to sort domestic and international tech-art integration theories), case analysis (e.g., Spider-Man: Into the Spider-Verse for real-time rendering, Love, Death & Robots for AI-assisted scripting, to deconstruct integration modes), and expert interviews (to collect insights from creation teams and R&D personnel). Results show intelligent technologies have widely penetrated character generation, scene construction, motion capture, and post-rendering, boosting efficiency and visual appeal. However, issues emerge: excessive tech use weakens artistic individuality, algorithm logic conflicts with aesthetics, and technical ethics disputes arise. Conclusions highlight that integration must follow “technology serving art”—via building tech-art collaboration mechanisms, strengthening interdisciplinary talent training, and improving ethics norms—to achieve dynamic balance. Contributions include enriching the tech-art integration theoretical system (offering new interdisciplinary perspectives for animation research) and providing actionable strategies for creators, aiding industrial innovation, and informing policy-making.